Banana bunchy top virus: Threat to musaceae in Latin America and the Caribbean - Martinez-Solórzano, Gustavo E.; Rey, Juan Carlos; Urias, Carlos; Lescot, Thierry; Roux, Nicolás; Salazar, Jesús; Rodríguez, Yamila (Agronomía Mesoamericana, 2022)
Introduction. Edible musaceae are considered strategic crops in the food security of many countries, and important in their economy and diet. However, they are threatened by various phytopathogenic organisms. Objective. To outline the significant features of Banana bunchy top virus (BBTV) caused by a virus of the family Nanoviridae, genus Babuvirus, which represents a potential threat to the musaseae production in Latin America and the Caribbean (LAC). Development. Musaceae are among the main foods and fruits produced in the world (among the six most important), and their commercialization defines them as the most exported fruits. It is estimated that 47 % of the pathogens that originate emerging and re-emerging diseases of global importance are viruses. Among them, BBTV is the most damaging viral disease for musaceae, with potential economic impact, in addition, it limits the international exchange of germplasm. This systemic pathogen is unlikely to be transmitted by agricultural implements, since it is not present in the soil. Its dissemination only occurs through: a) Insect vector Pentalonia nigronervosa, which spreads it over short distance, and b) by infected propagation material that can distribute it between continents, with devastating effects in all the countries where it has been reported. Conclusions. The introduction of new materials (clones) resistant to Foc TR4 (disease present in America) without proper supervision and quarantine measures, can promote the manipulation of in vitro plants carring the virus, which, when exposed to the action of the insect vector present in LAC, condition the entry and spread of the BBTV in this region (main of exporting countries), whose presence could be catastrophic and cause economic losses, similar to those that have occurred in producing countries that have been affected.